2020
DOI: 10.1002/oby.23001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Bariatric Surgery in Patients with End‐Stage Chronic Kidney Disease or Kidney Transplant

Abstract: ObjectiveThis study aimed to evaluate (1) the effectiveness, complications, and postoperative access to transplantation in end‐stage chronic kidney disease (ECKD) and (2) the effectiveness and complications of bariatric surgery in patients who had already undergone kidney transplant.MethodsA systematic review and meta‐analysis of mortality and complications rates were performed. Thirty studies were reviewed.ResultsAfter bariatric surgery, patients with ECKD had similar postoperative weight loss to patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…However, medical management could have limited long-term success, while bariatric surgery could offer a reliable strategy to achieve weight loss in kidney transplant candidates[ 21 , 33 ], with acceptable morbidity and mortality rates[ 34 - 36 ]. Bariatric surgery in ESRD patients is associated with weight loss ranging from 29.8% to 72.8% excess weight loss (%EWL)[ 37 ], with reported mortality and morbidity rates of 2% and 7%, respectively[ 37 ]. Complications associated with bariatric surgery are higher in ESRD patients than in non-ESRD patients[ 37 ]: The mortality rate (2%) observed in the ESRD population is approximately 10 times higher than the mortality rate (0.18%) reported in the general population[ 38 ], while the rate of postoperative complications in ESRD patients is significantly higher than that observed in accredited hospitals for bariatric surgery (0.17%)[ 39 ].…”
Section: Obesity and Esrdmentioning
confidence: 99%
See 2 more Smart Citations
“…However, medical management could have limited long-term success, while bariatric surgery could offer a reliable strategy to achieve weight loss in kidney transplant candidates[ 21 , 33 ], with acceptable morbidity and mortality rates[ 34 - 36 ]. Bariatric surgery in ESRD patients is associated with weight loss ranging from 29.8% to 72.8% excess weight loss (%EWL)[ 37 ], with reported mortality and morbidity rates of 2% and 7%, respectively[ 37 ]. Complications associated with bariatric surgery are higher in ESRD patients than in non-ESRD patients[ 37 ]: The mortality rate (2%) observed in the ESRD population is approximately 10 times higher than the mortality rate (0.18%) reported in the general population[ 38 ], while the rate of postoperative complications in ESRD patients is significantly higher than that observed in accredited hospitals for bariatric surgery (0.17%)[ 39 ].…”
Section: Obesity and Esrdmentioning
confidence: 99%
“…Bariatric surgery in ESRD patients is associated with weight loss ranging from 29.8% to 72.8% excess weight loss (%EWL)[ 37 ], with reported mortality and morbidity rates of 2% and 7%, respectively[ 37 ]. Complications associated with bariatric surgery are higher in ESRD patients than in non-ESRD patients[ 37 ]: The mortality rate (2%) observed in the ESRD population is approximately 10 times higher than the mortality rate (0.18%) reported in the general population[ 38 ], while the rate of postoperative complications in ESRD patients is significantly higher than that observed in accredited hospitals for bariatric surgery (0.17%)[ 39 ]. However, many studies have consistently shown that bariatric surgery in patients with chronic kidney disease (CKD) stage 1 and 2, is associated with slower epidermal growth factor receptor (eGFR) decline and lower risk of kidney failure[ 40 , 41 ].…”
Section: Obesity and Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also much interest in the possibility of bariatric surgery in either potential renal transplant candidates or post-renal transplant [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. Several studies have shown that bariatric surgery is safe and feasible in patients with ESKD and kidney transplant recipients [ 133 , 138 ].…”
Section: Obesitymentioning
confidence: 99%
“…Several studies have shown that bariatric surgery is safe and feasible in patients with ESKD and kidney transplant recipients [ 133 , 138 ]. It is also known to be effective and cause a significant reduction in BMI [ 135 ]. This itself in renal transplant candidates may improve outcomes based on the association between high BMI and increased post-operative complications.…”
Section: Obesitymentioning
confidence: 99%